Influencing factors to have an additional child by working women in Korea. Issue 2 (1st June 2018) - Chang, Insu; Kim, Brian H.S.
Abstract: This study aims to explore the effects of individual and regional characteristics on working women's intention of additional childbirth in Korea. Since most the individuals generally revolve within their own hierarchically structured regions, data from 2012 Population and Housing Census Statistics are utilized in the analysis. The hierarchical generalized liner model is employed to find out the effects of individual and regional factors, while comparisons of these results are made using the binary logistic model. And finally, Heckman 2-stage model is applied in order to determine if selection bias is present. The results indicate that the working women ultimately deal with economic aspects on their decision for additional childbirth. Regional characteristics variables, namely unemployment rate, city type, private education cost, workplace daycare facilities and government budget for childcare, reflect economic aspects in households. These findings address important policy implications to overcome low fertility rate in the era of increasing number of working women.